2005
DOI: 10.1002/jts.20061
|View full text |Cite
|
Sign up to set email alerts
|

Sexual revictimization among sexual minorities: A preliminary study

Abstract: The present study examined patterns of sexual assault and its psychological correlates among gay men, lesbians, and bisexual men and women (GLB). A community sample of 342 GLB individuals completed questionnaires assessing victimization history and psychological functioning. Nearly 63% of participants reported some form of sexual assault, and nearly 40% reported sexual revictimization, defined as contact or penetrative sexual assault reported in both childhood and adulthood. Gay men and bisexual men and women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 38 publications
7
97
0
Order By: Relevance
“…HIV-infected men who have sex with men (MSM) represent an additional population where PTSD is over-represented. In MSM, the most common trauma studied is CSA (Lenderking et al, 1997), and there is evidence that MSM with a history of CSA are more likely to be at risk for re-victimization through adult sexual assault (Heidt, Marx, & Gold, 2005). Among the many factors that contribute to HIV-infected vulnerability to PTSD, HIV-related stigma stands out as a key catalyst and precursor to interpersonal violence and trauma associated with PTSD (e.g., Breet, Kagee, & Seedat, 2014).…”
mentioning
confidence: 99%
“…HIV-infected men who have sex with men (MSM) represent an additional population where PTSD is over-represented. In MSM, the most common trauma studied is CSA (Lenderking et al, 1997), and there is evidence that MSM with a history of CSA are more likely to be at risk for re-victimization through adult sexual assault (Heidt, Marx, & Gold, 2005). Among the many factors that contribute to HIV-infected vulnerability to PTSD, HIV-related stigma stands out as a key catalyst and precursor to interpersonal violence and trauma associated with PTSD (e.g., Breet, Kagee, & Seedat, 2014).…”
mentioning
confidence: 99%
“…In fact, in the aforementioned emergency department study, the majority of men patients treated (61%) were between the ages of 0 and 9. The prevalence of men adult sexual assault is thought to be lower, between 0.8% and 7% (Elliott, Doris, & John, 2004;Sorenson, Stein, Siegel, Golding, & Burnam, 1987;Tjaden & Thoennes, 2006), with rates as high as 17% in gay or bisexual men (Heidt, Marx, & Gold, 2005) and 20% in men veterans being treated for combat-related posttraumatic stress disorder (Butterfield et al, 2005). However, a number of factors including differences in definitions of sexual assault and underreporting are likely to affect the accuracy of these statistics.…”
mentioning
confidence: 99%
“…Discrimination was positively associated with a diagnosis of any psychiatric disorder (OR = 1.6; Mays & Cochran, 2001). Heidt, Marx, and Gold (2005) found that 63% of lesbian, gay, and bisexual men and women had experienced some form of sexual violence and that sexual violence was associated with an increased risk of depression and PTSD. Herek, Gillis, and Cogan (1999) and Hershberger and D'Augelli (1995) also confirmed that gay-related harassment and physical abuse was associated with depression, anxiety, and other mental health…”
Section: Research Contextmentioning
confidence: 99%